تأثير تمرينات مصاحبة لبعض وسائل الاستشفاء في بعض القدرات البدنية للاعبين الشباب بكرة الطائرة - Mona Hamid Jassim (Mustansiriyah Journal of Sports Science, 2024)
The study aimed to identify the effect of exercises accompanied by therapeutic methods on players injured in the ankle joint of volleyball players, and the speed of their recovery, as most therapeutic methods take a long time during the treatment period, which negatively affects the players’ results. The researcher used the experimental approach in treating Research problems، As for the research community, the research community was identified with injured young players of Baghdad clubs participating in the Iraqi volleyball league for the 2022-2023 sports season who suffer from a minor sports injury to the players, according to the statements of the Sports Medicine Department, in addition to the diagnosis by a specialist doctor, which is numbered(12) players, and the research sample was chosen from them by (8) players, with a percentage of (66.66%) from the total research community. After the researcher completed the field research procedures using the scientific method of writing research, and after processing the obtained data statistically, she concluded several conclusions, including: - The exercises associated with recovery methods had an effective role in improving the speed of recovery - The exercises accompanying recovery methods played a major role in developing the strength of motor abilities. According to these conclusions, the researcher made several recommendations, including: - Paying attention to exercises that accompany the recovery methods for the body’s active muscles, as they have an effective role in improving the speed of recovery. -It is recommended to perform various exercises to prepare the body for rest, in order to avoid fatigue and stress. Relaxation and meditation exercises can be included to help restore calm and relaxation after strenuous training.